On dynamics of Lotka-Volterra type operators - Mukhamedov, Farrukh; Saburov, Mansoor (School of Mathematical Sciences, Universiti Sains Malaysia, 2014)
In the present paper, we study dynamics of Lotka-Volterra (LV) type operators defined in finite dimensional simplex. We introduce a new class of LV-type operators, called MLV type. Some concrete examples are also provided. We prove that trajectories of such kind of operators converge, and moreover, we find an estimation for fixed points of the introduced operators.